actualization of french experience in humanization of pedagogical education for ukraine: organization lessons. (Journal of Educational Sciences, 2016)
The publication deals with the topical for improving Ukrainian system of pedagogical education lessons of humanization of French professional training of teachers in the organizational aspect. Under the humanization of the pedagogical education «is the organization of the pedagogical process, which is aimed at development of the individual personality of the teacher and involves the formation of his mechanisms of self-education and self-education by meeting basic needs in education. The purpose of pedagogical training of French scientists sees ways to help develop the personality of the teacher, which has both a new style of pedagogical thinking,i.e. pedagogical reflection and high professionalism The main author’s attention is paid to opening prospects of cooperation of internal and external participants of pedagogical process in reforming the system of pedagogical education in the context of humanization; performing professional training of teachers in conditions of specialized higher educational pedagogical establishments; gaining pedagogical education on the base of the diploma of basic higher education; development of the selection system for the youth, prone to pedagogical profession. To organizational lesson the author regards the following: (1) the cooperation of the education system with the national Union of teachers, universities, mass media, political parties, public opinion, the administration at the local level; (2) the establishment of the University Institute of teacher training; (3) introduction of competitive examinations for future teachers. The prospect of further scientific research in the definition of didactic (substantive and procedural) lessons from the French experience of humanization of the pedagogical education for the improvement of the Ukrainian system of professional training of teachers at the present stage.
Keywords: humanization; pedagogical education in France; personality of teacher; institute of University training of teachers